2001
DOI: 10.1590/s0104-11692001000400013
|View full text |Cite
|
Sign up to set email alerts
|

Breve reflexão sobre autocuidado no planejamento de alta hospitalar pós-Transplante de medula óssea (TMO): relato de caso

Abstract: Silva LMG. Breve reflexão sobre autocuidado no planejamento de alta hospitalar pós-transplante de medula óssea (TMO) (1) . É indicado em patologias malignas ou não, modificando significativamente o prognóstico de pacientes portadores de doenças que, até alguns anos atrás, eram fatais. Entretanto, o TMO é um procedimento agressivo, de alto custo financeiro, acarretando severos efeitos colaterais, além de outras complicações e fatores de tensão físicos e psicológicos vivenciados pelo paciente e família (2) . Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
10

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 4 publications
0
7
0
10
Order By: Relevance
“…These showed how this theory is applicable and how it can contribute to the development of nursing work. Some of these are: A case study that identified nursing diagnoses in high-risk pregnant women based on the self-care theory, highlighting the importance of accomplishing the nursing process and the possibility of stimulating self-care in these customers (1) ; A case report regarding self-care in planning hospital discharge after bone marrow transplantation (2) ; A qualitative study that used the self-care deficit theory in hypertensive women, stressing its contribution in the detection of aspects nurses can explore and which can contribute to arterial hypertension treatment (3) ;…”
Section: Introductionmentioning
confidence: 99%
“…These showed how this theory is applicable and how it can contribute to the development of nursing work. Some of these are: A case study that identified nursing diagnoses in high-risk pregnant women based on the self-care theory, highlighting the importance of accomplishing the nursing process and the possibility of stimulating self-care in these customers (1) ; A case report regarding self-care in planning hospital discharge after bone marrow transplantation (2) ; A qualitative study that used the self-care deficit theory in hypertensive women, stressing its contribution in the detection of aspects nurses can explore and which can contribute to arterial hypertension treatment (3) ;…”
Section: Introductionmentioning
confidence: 99%
“…A base para tomada de decisões da enfermagem é o julgamento clínico, que consiste em um processo mental norteado pelos princípios da ciência e determinado pelo conhecimento, experiência, percepção e intuição do enfermeiro que procura fazer julgamentos com bases em evidências, o qual leva ao diagnóstico de enfermagem (3) . Alguns pesquisadores comprovaram a coerência da aplicabilidade da Teoria do déficit de autocuidado juntamente com os diagnósticos de enfermagem da NANDA, sendo que tais modelos conceituais foram aplicados com êxito na prática de enfermagem em diferentes especialidades (13,14) -no cuidado a mulheres hipertensas em tratamento ambulatorial (15) ; na identificação de diagnósticos de enfermagem em idosos hipertensos (16) ; em portador de epilepsia (17) ; planejamento na alta hospitalar de pacientes submetidos ao transplante de medula óssea (18) ; em gestantes de baixo risco (13) ; em adolescentes grávidas (19) e pacientes submetidos ao cateterismo cardíaco (20) . Nesse sentido, o objetivo desse estudo foi determinar os diagnósticos de enfermagem da taxonomia II da NANDA em clientes submetidos ao cateterismo cardíaco, nas primeiras seis horas após o exame, a partir de julgamento clínico de enfermagem fundamentado na Teoria do Déficit de autocuidado, bem como avaliar se essa modalidade de julgamento clínico facilita a identificação dos referidos Diagnósticos de Enfermagem.…”
Section: Introductionunclassified
“…Educating for self-care is essential so that continuity of care at home as well as quality of treatment and patients' quality of life are ensured, despite all changes that a cancer treatment might cause in the families' routine. Emphasis on self-care implies individuals are active in the decision-making process to identify needs, the nature and actions that have to be developed in health care (16) .…”
Section: Results and Analysismentioning
confidence: 99%
“…A good nutritional condition offers the substrates necessary for the recovery process. It is important that family members know that there are important food restrictions aimed to prevent infections that can be acquired by the ingestion of inadequately prepared food (16) .…”
Section: Results and Analysismentioning
confidence: 99%